Keanekaragaman Lumut di Kawasan Cagar Alam Dungus Iwul, Jasinga, Jawa Barat - Florentina Indah Windadri (Universitas Atma Jaya Yogyakarta, 2010)
Exploration and collection of the mosses species in Dungus Iwul Nature Reserve were conducted. Thirty eight species including 26 genera and 11 families were recorded. Three species had categories as endemic species i.e Fissidens teysmannianus and Orthomnion javense as endemic species in Java and Hyophila javensis as endemic species in Malesia. Ctenidium lychnites was recorded also as new species record in Java.